2011
DOI: 10.1089/ars.2010.3356
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility Group Box 1, Oxidative Stress, and Disease

Abstract: Oxidative stress and associated reactive oxygen species can modify lipids, proteins, carbohydrates, and nucleic acids, and induce the mitochondrial permeability transition, providing a signal leading to the induction of autophagy, apoptosis, and necrosis. High-mobility group box 1 (HMGB1) protein, a chromatin-binding nuclear protein and damage-associated molecular pattern molecule, is integral to oxidative stress and downstream apoptosis or survival. Accumulation of HMGB1 at sites of oxidative DNA damage can l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
363
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(385 citation statements)
references
References 268 publications
(240 reference statements)
8
363
0
5
Order By: Relevance
“…Aggregation of a fragment of Htt protein directly causes free radical production in vivo (36), and inhibition of polyQ aggregation suppresses ROS (50,51). Oxidative potential is important for the nucleocytoplasmic translocation of HMGB1, and redox status of HMGB1 also affects its specific function (52). In our study, ROS generated by overexpression of 97Q-GFP induced translocation of nuclear HMGB1.…”
Section: Discussionmentioning
confidence: 51%
“…Aggregation of a fragment of Htt protein directly causes free radical production in vivo (36), and inhibition of polyQ aggregation suppresses ROS (50,51). Oxidative potential is important for the nucleocytoplasmic translocation of HMGB1, and redox status of HMGB1 also affects its specific function (52). In our study, ROS generated by overexpression of 97Q-GFP induced translocation of nuclear HMGB1.…”
Section: Discussionmentioning
confidence: 51%
“…HMGB1 is a chromatin-associated nuclear protein and extracellular damage-associated molecular pattern molecule. 47,48 Recently, we have shown that HMGB1 is a novel Beclin 1-binding protein important in sustaining autophagy. 25,49 Deletion, depletion or inhibition of HMGB1 in mouse embryonic fibroblasts or tumor cells markedly diminishes autophagy.…”
Section: Other Beclin 1-binding Proteins In Autophagymentioning
confidence: 99%
“…Using a unique NMR-based approach, we have investigated the kinetics of HMGB1 oxidation and the half-lives of all-thiol and disulfide HMGB1 species in serum, saliva, and cell culture medium. In this approach, salt-free lyophilized 15 Nlabeled all-thiol HMGB1 was dissolved in actual extracellular fluids, and the oxidation and clearance kinetics were monitored in situ by recording a series of heteronuclear 1 H-15 N correlation spectra. We found that the half-life depends significantly on the extracellular environment.…”
mentioning
confidence: 99%
“…This 25-kDa protein, which is normally located in nuclei, is passively released during cell injury and necrosis and actively secreted by some cell types via a non-canonical pathway that bypasses the endoplasmic reticulum (13,14). Extracellular HMGB1 acts as a danger signal and inflammatory mediator via binding to cell surface receptors such as RAGE, TLR4 (Toll-like receptor 4), and CXCR4 (13)(14)(15)(16). Extracellular HMGB1/receptor interactions promote inflammation and angiogenesis via activation of NF-B (17,18) and tumor proliferation via activation of p44/ p42, p38, and SAPK/JNK MAPKs (19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation